Interleukin‐6 Deficiency Corrects Nephritis, Lymphocyte Abnormalities, and Secondary Sjögren's Syndrome Features in Lupus‐Prone Sle1.Yaa Mice1. Issue 9 (September 2014) - Maier‐Moore, Jacen S.; Horton, Christopher G.; Mathews, Shirley A.; Confer, Anthony W.; Lawrence, Christina; Pan, Zijian; Coggeshall, K. Mark; Farris, A. Darise
<x xml:space="preserve">Abstract</x> Objective To assess disease features in Sle1.Yaa mice with genetic interleukin‐6 (IL‐6) deficiency. Methods Sera and tissues were collected from C57BL/6 (B6), Sle1.Yaa, and Sle1.Yaa.IL‐6−/− mice and analyzed for various features of disease. Using serum samples, autoantibody specificities were determined by enzyme‐linked immunosorbent assay (ELISA) and indirect immunofluorescence, cytokine production was analyzed by Luminex and ELISA, and levels of blood urea nitrogen were determined by ELISA. Renal, lung, and salivary gland tissue sections were evaluated for pathologic changes. Lymphocyte phenotypes, including CD4+ T cell cytokine production, and those of follicular and extrafollicular T helper subsets, germinal center B cells, and plasma cells, were determined using flow cytometry. Results IL‐6 deficiency not only ameliorated autoantibody production and renal disease in this model, but also effectively reduced inflammation of lungs and salivary glands. Furthermore, IL‐6 deficiency abrogated differentiation of Th1 and extrafollicular T helper cells, germinal center B cells, and plasma cells in the spleen and eliminated renal T cells with IL‐17, interferon‐γ, and IL‐21 production potential. Conclusion Our findings highlight IL‐6–mediated T cell aberrations in Yaa‐driven autoimmunity and support the concept of therapeutic IL‐6/IL‐6 receptor blockade in systemic lupus erythematosus and Sjögren's syndrome by impairing the production of autoantibodies and lymphocytic infiltration of the kidneys, lungs, and salivary glands.